ДОСЛІДЖЕННЯ РЕЖИМІВ КОМПЕНСАЦІЇ РЕАКТИВНОЇ ПОТУЖНОСТІ В СИСТЕМІ ЕЛЕКТРОПОСТАЧАННЯ З КАСКАДОМ ТРАНСФОРМАТОРІВ - Ягуп, В.Г.; Ягуп, К.В. (Інститут електродинаміки НАН України, Київ, 2025)
The modes of reactive power compensation in the power supply system powered by a synchronous generator through a cascade of intermediate transformers have been studied. It is shown that the reactive component of the common complex resistance of the generator and the power transmission path can cause relatively large levels of reactive power in the system. Experiments show that this power remains in the system even after the application of transverse capacitive compensation, which is not able to provide full compensation of reactive power in a power supply system with a cascade of transformers. Under these conditions, the optimal value of the capacitance of the transverse compensation capacitor was found using the search optimization method on the computer model. The results of the study show the possibility of achieving the mode of full compensation of reactive power due to a relatively small increase in the capacity of the compensating capacitor, which provides transverse compensation. References 8, figures 6, table1.